Experimental Investigation of the Hydrate-Based Gas Separation of Synthetic Flue Gas with 5A Zeolite - Xiaoya Zang; Na Zhang; Xuebing Zhou; Lihua Wan; Deqing Liang (Energies, 2020)
Coal combustion flue gas contains CO2, a greenhouse gas and driver of climate change. Therefore, CO2 separation and removal is necessary. Fortunately, 5A zeolites are highly porous and can be used as a CO2 adsorbent. In addition, they act as nuclei for hydrate formation. In this work, a composite technology, based on the physical adsorption of CO2 by 5A zeolite and hydrate-based gas separation, was used to separate CO2/N2 gas mixtures. The influence of water content, temperature, pressure, and particle size on gas adsorption and CO2 separation was studied, revealing that the CO2 separation ability of zeolite particles sized 150–180 μm was better than that of those sized 380–830 μm at 271.2 K and 273.2 K. When the zeolite particles were 150–180 μm (type-B zeolite) with a water content of 35.3%, the gas consumption per mole of water (<semantics>ngas/nH2O</semantics> ) reached the maximum, 0.048, and the CO2 separation ratio reached 14.30%. The CO2 molar concentration in the remaining gas phase (<semantics><msubsup>xCO2gas</msubsup></semantics>) was lowest at 271.2 K in the type-B zeolite system with a water content of 47.62%. Raman analysis revealed that CO2 preferentially occupied the small hydrate cages and there was a competitive relationship between N2 and CO2.